CRISPR/Cas9: Implications for Modeling and Therapy of Neurodegenerative Diseases - Yang, Weili; Tu, Zhuchi; Sun, Qiang; Li, Xiao-Jiang (Frontiers in Molecular Neuroscience, 2016)
CRISPR/Cas9 is now used widely to genetically modify the genomes of various species. The ability of CRISPR/Cas9 to delete DNA sequences and correct DNA mutations opens up a new avenue to treat genetic diseases that are caused by DNA mutations. In this review, we describe the advantages of using CRISPR/Cas9 to engineer genomic DNAs in animal embryos, as well as in specific regions or cell types in the brain. We also discuss how to apply CRISPR/Cas9 to establish animal models of neurodegenerative diseases, such as Parkinson’s and Huntington's diseases, and to treat these disorders that are caused by genetic mutations.